Turkish students’ academic adjustment in Russian-medium degree programs: Academic Russian proficiency, social support, and institutional contexts - Ülgen, Hamza (Journal of International Students, 2026)
This qualitative study examines how academic Russian, institutional conditions, and social support shape the academic adjustment of Turkish undergraduate and graduate students enrolled in Russian-medium degree programs in Moscow. Drawing on phenomenologically informed, semistructured interviews with 15 students at three universities, we used reflexive thematic analysis and a study-specific 4A framework (Access, Amplification, Authentication, Awareness) to interpret their experiences. Dense academic Russian, opaque bureaucratic procedures and formal, teacher-centered classroom norms constrained participation, while peers, conational networks and digital platforms provided multilayered support that sustained engagement. Academic Russian functioned as an epistemic threshold regulating entry into disciplinary knowledge, and bureaucratic formality operated as an integration cost that raised the effort required to persist. The findings extend classic models of acculturation, academic integration and social support by showing how social support infrastructures and institutional arrangements jointly shape international students’ opportunities to learn and remain in non-Anglophone, Russian-medium programs.